THE PARTICIPATION OF PARENTS IN THE IMPLEMENTATION OF GMIM KINILOW SCHOOL EDUCATION IN TOMOHON CITY - POLA, BELLAFISKA; RORONG, ARIE; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2020)
This study aims to determine the participation of parents in the administration of Kinilow GMIM PrimarySchool Education in the City of Tomohon. This research uses the theory of Epstein (2001) which categorizesparents' participation into six types of involvement, namely: parenting, communication, volunteering,learning from home, decision making, working with the community. participation is the involvement of aperson or several people in an activity. Involvement can be in the form of mental and emotional as well asphysical involvement in using all the capabilities it has (taking the initiative) in all activities carried out aswell as supporting the achievement of objectives and responsibilities for all engagements. Participation is themental and emotional involvement of a person in a group situation. This study used qualitative researchmethods. The qualitative research method in this research is a method that aims to explain or describe theproblem systematically, factually and accurately about the facts and characteristics of the population of aparticular area. Data collection techniques used are 1) Interview is a question and answer process inresearch that takes place orally. Interviews can function in a descriptive manner that is to describe the worldof reality as experienced by others. 2) Observation is used to obtain data on parent participation in thedelivery of educational services. 3) Documentation is data collection by viewing and recording existingdocuments. In this study there are various problems that arise, namely parenting from both parties from theschool as well as the family or parents must go hand in hand so that it can make children more comfortablein carrying out tasks, then good communication to children will make children feel noticed so there isopenness between children and parents, and then from the other 4 aspects must complement each other inorder to achieve a good cooperation between the parents and the school in the child development.Keywords: Participation, Organization, Education